The Correlation Between Parents’ Self-Determination with Behavioral Prevention of Picky Eating in Toddlers - Dona Muji Fitriana; Yuni Sufyanti Arief; Ilya Krisnana (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2020)
Introduction: Picky eating is a disorder in eating patterns which is currently found in toddlers and parents have an important role in shaping the eating behavior of children. The purpose of this study was to determine the correlation of parents' self-determination with the behavioral prevention of picky eating in toddlers. Methods: This study is a correlational analytic study with cross-sectional design. The independent variable in this study is parents’ self-determination and the dependent variable is behavioral prevention of picky eating. The population was parents with toddlers in the working area at the Public Health Center of Kedawung 1, Sragen, Central Java. A sample of 113 respondents was selected by cluster sampling. Data were collected using questionnaires demographic of the respondent, Basic Psychological Need Satisfaction and Frustration Scale/BPNSFS, and behavioral prevention of picky eating which was then analyzed using the Spearman-rank test. Results: Based on the characteristics, the majority of respondents are aged 21-39 years old, educated from junior to senior high, working as a housewife, and have a family income each month was less than the minimum wage of work. The results showed that most parents with self-determination in the good category correlate positively with the behavioral prevention of picky eating in their children (p value=0.000, r-value=0.487). Conclusion: Parents with self-determination in the good category also have good behavioral prevention of picky eating. The result of this study could be used by nurses to reference in health promotion into the prevention of picky eating in children.